2019
DOI: 10.1038/s41526-019-0083-2
|View full text |Cite
|
Sign up to set email alerts
|

Role of hydrostatic pressure and wall effect in solidification of TC8 alloy

Abstract: The solidification experiments of TC8 alloy under both microgravity and normal gravity were conducted using a drop tube. The solidification microstructure were found composed of fine equiaxed grains formed at early stage and bigger elongated grains formed at later stage. Between the two kinds of grains a curved transition interface was observed in 1g sample, while that in μg sample was almost flat. Generally, the amounts and aspect ratios of the grains are larger, and the grain sizes are smaller in 1g sample. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Microgravity is an excellent environment to inhibit the convection. 2528 Since the 1970s, solidification experiments have been carried out under microgravity conditions of space to obtain immiscible alloys with a dispersed microstructure. For example, in 1978, Carlberg et al 29 performed solidification experiments with the Zn-Bi immiscible alloys on the second TEXUS flights and found that the phase macro-segregation occurs during the solidification.…”
Section: Introductionmentioning
confidence: 99%
“…Microgravity is an excellent environment to inhibit the convection. 2528 Since the 1970s, solidification experiments have been carried out under microgravity conditions of space to obtain immiscible alloys with a dispersed microstructure. For example, in 1978, Carlberg et al 29 performed solidification experiments with the Zn-Bi immiscible alloys on the second TEXUS flights and found that the phase macro-segregation occurs during the solidification.…”
Section: Introductionmentioning
confidence: 99%